A wear-resistant drag chain protective material and its preparation method and application
The wear-resistant drag chain protection material prepared by multi-step processing, combined with the use of tetrafluoro emulsion and perfluoropolyether lubricant, solved the problem of insufficient wear resistance of drag chain protection structures in the prior art, and significantly improved the use of materials Lifespan and wear resistance.
Patent Information
- Application Number
- CN202411355574.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The existing dust-free cable drag chain protection structure has a short service life due to friction during application and has limited wear resistance.
The material with a mass ratio of 4:1 to 6:1 to extrusion molding, calendering, stretching, sintering and forming are used to prepare wear-resistant drag chain protection materials. And coat the outer surface of the material with tetrafluoro emulsion and the inner surface with perfluoropolyether lubricating oil to improve wear resistance.
By reducing the friction coefficient, the service life of the material is increased, and the lubricant is prevented from precipitating through the curing of the tetrafluoro emulsion, the working time is extended, and the cleanliness and wear resistance of the material are improved.
Smart Images

Figure CN119039642B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cable materials, and in particular to a wear-resistant drag chain protective material and a preparation method and application thereof. Background Art
[0002] The existing dust-free cable drag chain protection structure is made of a composite of polymer materials polyurethane (PU) and expanded polytetrafluoroethylene products (e-EPTFE). However, the dust-free cable drag chain protection structure made of polyurethane and expanded polytetrafluoroethylene products will be in dry friction with the cable body inside for a long time during the application process. The friction can only be protected by the wear resistance of the e-EPTFE material itself, which has limited wear resistance and a short service life.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The object of the present invention is to provide a wear-resistant drag chain protective material and a preparation method and application thereof, so as to solve or improve the above-mentioned technical problems.
[0005] The present invention can be implemented like this:
[0006] In a first aspect, the present invention provides a method for preparing a wear-resistant drag chain protective material, comprising the following steps: mixing a polytetrafluoroethylene dispersion resin and a propellant and then extruding to obtain an extruded base belt; calendering the extruded base belt to obtain a calendered belt; removing the propellant in the calendered belt, and then stretching to obtain a stretched film; winding the stretched film on a hard part and performing a first pressing, and then performing a first sintering and shaping to obtain a first shaping material; performing a second pressing on the first shaping material, and then performing a second sintering and shaping to obtain a second shaping material; coating a tetrafluoro emulsion on the outer surface of the second shaping material and curing it, and then coating a perfluoropolyether lubricating oil on the inner surface of the secondary shaping material;
[0007] The mass ratio of polytetrafluoroethylene dispersion resin to propellant is 4:1 to 6:1;
[0008] The pressure of the first pressing is 0.2MPa~1MPa, and the time of the first pressing is 1min~2min;
[0009] The temperature of the first sintering is 350℃~380℃, and the time of the first sintering is 15min~30min;
[0010] The pressure of the second pressing is 0.5MPa~1.5MPa, and the time of the second pressing is 2min~3min;
[0011] In an optional embodiment, the temperature of the second sintering and shaping is 350° C. to 380° C., and the time of the second sintering and shaping is 15 min to 30 min.
[0012] The solid content of PTFE emulsion is 45%~65%, and the coating amount of PTFE emulsion is 250mL / m 2 ~350mL / m 2 ;
[0013] The coating amount of perfluoropolyether lubricant is 150mL / m 2 ~250mL / m 2 .
[0014] In an optional embodiment, the propellant includes at least one of an alkane solvent, kerosene, petroleum ether and paraffin.
[0015] In an optional embodiment, the extrusion molding pressure is 30 bar to 40 bar.
[0016] In an optional embodiment, the thickness of the calendered tape is 0.5 mm to 0.7 mm.
[0017] In an optional embodiment, the stretching process includes transverse stretching and longitudinal stretching;
[0018] The transverse stretching is performed at a stretching ratio of 8 to 10 times and at a temperature of 250°C to 280°C.
[0019] The longitudinal stretching has a stretching ratio of 12 to 16 times, and the longitudinal stretching is performed at a temperature of 320°C to 400°C.
[0020] In an optional embodiment, the curing temperature is 220° C. to 245° C., and the curing time is 15 min to 30 min.
[0021] In an optional embodiment, the molecular weight of the perfluoropolyether lubricant is 10000 g / mol to 15000 g / mol.
[0022] In a second aspect, the present invention provides a wear-resistant drag chain protective material, which is prepared by the preparation method of any one of the aforementioned embodiments.
[0023] In a third aspect, the present invention provides a cable, comprising a cable body, the surface of which is provided with a wear-resistant layer prepared from the wear-resistant drag chain protective material of the aforementioned embodiment.
[0024] In an optional embodiment, the cable is a drag chain cable, the drag chain cable also includes a drag chain, and the wear-resistant layer is connected to the inner side of the drag chain.
[0025] The beneficial effects of the present invention include:
[0026] The present invention can change the dry friction between the wear-resistant drag chain protection material and the internal filling components (such as cables or air pipes, etc.) into wet friction by coating perfluoropolyether lubricating oil on the inner surface of the second shaping material, thereby reducing the friction coefficient and increasing the service life of the material; and can effectively prevent the perfluoropolyether lubricating oil on the inner side of the second shaping material from precipitating to the outside by coating tetrafluoro emulsion on the outer side of the outer surface of the second shaping material and performing high-temperature curing. On the one hand, the perfluoropolyether lubricating oil can be confined to the inside of the second shaping material to extend its action time, and on the other hand, the cleanliness of the surface of the wear-resistant drag chain protection material can be improved to achieve dust-free protection.
[0027] The preparation method of the wear-resistant drag chain protective material provided by the present invention is simple and easy to operate, and can effectively reduce the friction coefficient between the drag chain and the protective device. The obtained wear-resistant drag chain protective material has high density, good flexibility, smooth and wear-resistant surface, and high wear resistance, and is particularly suitable for dust-free tank drag chain cables. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 This is a SEM image of the surface of the wear-resistant drag chain protective material in Example 1;
[0030] Figure 2 This is a SEM image of the cross section of the wear-resistant drag chain protective material in Example 1;
[0031] Figure 3 This is a SEM image of the surface of a commercially available dust-free drag chain cable protection material;
[0032] Figure 4 for Figure 3 A magnified image of
[0033] Figure 5 This is a graph showing the wear resistance test results of the second shaping material in Example 1;
[0034] Figure 6 This is a diagram showing the wear resistance test results of the wear-resistant drag chain protective material in Example 1;
[0035] Figure 7 The figure shows the wear resistance test results of commercially available dust-free drag chain cable protection materials. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0037] The wear-resistant drag chain protective material provided by the present invention and its preparation method and application are described in detail below.
[0038] The invention provides a preparation method of a wear-resistant drag chain protective material, comprising the following steps: mixing a polytetrafluoroethylene dispersion resin and a propellant and then extruding and molding the mixture to obtain an extruded base belt; calendering the extruded base belt to obtain a calendered belt; removing the propellant in the calendered belt and then stretching the mixture to obtain a stretched film; winding the stretched film on a hard part and performing a first pressing, and then performing a first sintering and shaping to obtain a first shaping material; performing a second pressing on the first shaping material and then performing a second sintering and shaping to obtain a second shaping material; coating a tetrafluoro emulsion on the outer surface of the second shaping material and curing the mixture, and then coating a perfluoropolyether lubricating oil on the inner surface of the secondary shaping material.
[0039] In some optional embodiments, the mass ratio of the polytetrafluoroethylene dispersion resin to the propellant can be 4:1 to 6:1, such as 4:1, 4.5:1, 5:1, 5.5:1 or 6:1, or other values within the range of 4:1 to 6:1.
[0040] If the mass ratio of polytetrafluoroethylene dispersion resin to propellant is less than 4:1 (such as 2:1), it is easy to cause a high solvent content inside the material, reducing resistance during extrusion, reducing the extrusion fiberization degree of the material and the initial strength of the material; if the mass ratio of polytetrafluoroethylene dispersion resin to propellant is greater than 6:1 (such as 8:1), it is easy to cause a low solvent content inside the material, increasing resistance during extrusion, making the material difficult to extrude and destroying the material structure.
[0041] In some optional embodiments, the propellant may include, by way of example but not limitation, at least one of an alkane solvent, kerosene, petroleum ether, and paraffin. In some preferred embodiments, the propellant may be an alkane solvent, preferably an isoalkane solvent. In some more typical embodiments, the flash point of the isoalkane solvent is 50°C to 80°C, and the density is 600 kg / m 3 ~900kg / m 3 , the distillation range is an initial distillation point ≥ 184°C, a final distillation point ≤ 199°C, and a molecular weight of 150 g / mol to 200 g / mol. For example, the isoparaffin solvent may be ISOPAR L or the like.
[0042] By adopting the above-mentioned booster and controlling the mass ratio of the booster to the polytetrafluoroethylene dispersed resin to 1:4 to 1:6, the processing performance of the product is improved, the damage to the resin fiber during the processing is avoided, and the strength and other properties of the product are improved.
[0043] Furthermore, a mixed raw material obtained by mixing the polytetrafluoroethylene dispersion resin and the propellant is extruded through a mold to obtain an extruded base tape.
[0044] In some optional embodiments, the extrusion molding pressure may be 30 bar to 40 bar, such as 30 bar, 35 bar or 40 bar, etc., or may be other values within the range of 30 bar to 40 bar.
[0045] Furthermore, the extruded base tape is calendered by a calendering device to obtain a calendered tape.
[0046] In some optional embodiments, the thickness of the calendered tape may be 0.5 mm to 0.7 mm, such as 0.5 mm, 0.55 mm, 0.6 mm, 0.65 mm or 0.7 mm, etc., or may be other values within the range of 0.5 mm to 0.7 mm.
[0047] If the thickness of the calendered belt is too thin, it will easily lead to low strength in the longitudinal and transverse directions, which may easily cause material damage during longitudinal and transverse stretching; if the thickness of the calendered belt is too thick, it will lead to high strength in the longitudinal and transverse directions, and the material will not be able to stretch during longitudinal and transverse stretching, and cannot meet the requirements of subsequent processes.
[0048] Furthermore, the propellant in the calendered belt can be removed by using a conventional method according to the type of propellant actually used.
[0049] Taking the use of alkane solvents as the booster as an example, the alkane solvents can be evaporated and completely removed by heating at 100°C to 220°C. Preferably, during the heating process, the temperature in the degreasing box is a stepped area (for example, the temperature distribution is stepped from 100°C to 220°C and heated in 10°C intervals) to ensure that the solvent evaporates completely and does not have an adverse effect on the calendering belt.
[0050] Furthermore, the calendered belt from which the propellant is removed is subjected to a stretching treatment to obtain a stretched film.
[0051] The stretching process includes transverse stretching and longitudinal stretching.
[0052] The stretching ratio of the transverse stretching can be 8 to 10 times, such as 8 times, 8.5 times, 9 times, 9.5 times or 10 times, etc., or other values within the range of 8 to 10 times.
[0053] Transverse stretching can be performed at 250°C to 280°C. The temperature can be, for example, 250°C, 255°C, 260°C, 265°C, 270°C, 275°C or 280°C, or other values within the range of 250°C to 280°C.
[0054] The stretching ratio of the longitudinal stretching can be 12 to 16 times, such as 12 times, 12.5 times, 13 times, 13.5 times, 14 times, 14.5 times, 15 times, 15.5 times or 16 times, or other values within the range of 12 to 16 times.
[0055] Longitudinal stretching can be carried out under the condition of 320℃~400℃, and the temperature can be, for example, 320℃, 330℃, 340℃, 350℃, 360℃, 370℃, 380℃, 390℃ or 400℃, or other values within the range of 320℃~400℃.
[0056] It should be noted that in the prior art, the transverse stretching ratio of the relevant calendered belt is approximately 2 to 6 times, and the longitudinal stretching ratio is approximately less than 10 times. The present invention, through specific raw materials, specific extrusion pressure, specific calendering thickness, specific propellant removal method and specific stretching temperature, can make the transverse stretching ratio of the calendered belt reach 8 to 10 times and the longitudinal stretching ratio reach 12 to 16 times, which is beneficial to improve the density and strength and other properties of the wear-resistant drag chain protective material.
[0057] In some embodiments, the stretched film has a thickness of about 20 μm to about 30 μm.
[0058] Further, the stretched film obtained by stretching is wound and then pressed for the first time.
[0059] Exemplarily, the winding may be performed in a winding manner, and the hard member may be, for example, a steel roller.
[0060] The thickness after winding can be 0.8 mm to 1.0 mm, such as 0.8 mm, 0.85 mm, 0.9 mm, 0.95 mm or 1.0 mm, etc., and can also be other values within the range of 0.8 mm to 1.0 mm.
[0061] In some embodiments, the pressure of the first pressing is 0.2 MPa to 1 MPa, such as 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa or 1 MPa, etc., and may also be other values within the range of 0.2 MPa to 1 MPa.
[0062] If the pressure of the first pressing is too small, it will not be conducive to the discharge of gas inside the material. Gas will be easily generated inside the material during shaping, resulting in reduced bonding between material layers. If the pressure of the first pressing is too large, the thickness of the material will be reduced, which is not conducive to use.
[0063] The first pressing time can be 1min~2min, such as 1min, 1.5min or 2min.
[0064] Furthermore, after the first pressing, a first sintering and shaping process is performed, and this process can be performed in a high-temperature furnace, for example.
[0065] In some embodiments, the temperature of the first sintering can be 350°C to 380°C, such as 350°C, 355°C, 360°C, 365°C, 370°C, 375°C or 380°C, or other values within the range of 350°C to 380°C.
[0066] The time for the first sintering and shaping can be 15 minutes to 30 minutes, such as 15 minutes, 20 minutes, 25 minutes or 30 minutes, or other values within the range of 15 minutes to 30 minutes.
[0067] Through the above sintering and shaping conditions, the crystal structure of the material can be broken, the resin fibers can be connected together, and the density and strength of the material can be improved.
[0068] Furthermore, a second pressing is performed after the first sintering and shaping.
[0069] In some embodiments, the pressure of the second pressing can be 0.5 MPa to 1.5 MPa, such as 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa, 1 MPa, 1.1 MPa, 1.2 MPa, 1.3 MPa, 1.4 MPa or 1.5 MPa, etc., or other values within the range of 0.5 MPa to 1.5 MPa.
[0070] In some optional embodiments, the pressure of the second pressing can be the same as the pressure of the first pressing. In some preferred embodiments, the pressure of the second pressing is not less than the pressure of the first pressing.
[0071] The second pressing time can be 2min~3min, such as 2min, 2.5min or 3min.
[0072] Furthermore, a second sintering and shaping is performed after the second pressing.
[0073] In some embodiments, the temperature of the second sintering can be 350°C to 380°C, such as 350°C, 355°C, 360°C, 365°C, 370°C, 375°C or 380°C, or other values within the range of 350°C to 380°C.
[0074] The time for the second sintering and shaping can be 15 minutes to 30 minutes, such as 15 minutes, 20 minutes, 25 minutes or 30 minutes, or other values within the range of 15 minutes to 30 minutes.
[0075] It should be noted that the present invention can improve the density and strength of polytetrafluoroethylene materials by performing a second pressing and a second sintering after the first pressing and the first sintering, compared with the one-time pressing method used in the prior art. Even if the time of the one-time pressing method in the prior art is extended or the pressure of the first pressing is further increased, the effect of the second pressing of the present invention cannot be achieved.
[0076] Furthermore, a polytetrafluoroethylene emulsion is coated on the outer surface of the second shaping material and then cured.
[0077] Exemplarily, the coating may be performed by spraying.
[0078] The solid content of the tetrafluoro emulsion can be 45% to 65%, such as 45%, 50%, 55%, 60% or 65%, etc., or other values within the range of 45% to 65%. In some preferred embodiments, the solid content of the tetrafluoro emulsion is 40% to 60%. In some more preferred embodiments, the solid content of the tetrafluoro emulsion is 60%.
[0079] Accordingly, the coating amount of PTFE emulsion can be 250mL / m 2 ~350mL / m 2 , such as 250mL / m 2 , 260mL / m 2 , 270mL / m 2 , 280mL / m 2 , 290mL / m 2 、300mL / m 2 、310mL / m 2 、320mL / m 2 、330mL / m 2 、340mL / m 2 or 350 mL / m 2 etc., or 250mL / m 2 ~350mL / m 2 Other values within the range.
[0080] It should be noted that if the solid content of the PTFE emulsion is too high or the coating amount of the PTFE emulsion is too high, the uniformity of the material after spraying will be poor, which will affect the product performance; if the solid content of the PTFE emulsion is too low, on the one hand, it will lead to prolonged curing time and increased curing temperature, and on the other hand, it will also lead to an increase in the spraying amount, which will significantly increase the production cost and make it difficult to control the spraying effect.
[0081] In some embodiments, the curing temperature may be 220°C to 245°C, such as 220°C, 225°C, 230°C, 235°C, 240°C or 245°C, or other values within the range of 220°C to 245°C.
[0082] The curing time may be 15 min to 30 min, such as 15 min, 20 min, 25 min or 30 min, etc., or may be other values within the range of 15 min to 30 min.
[0083] Furthermore, perfluoropolyether lubricating oil is coated on the inner surface of the second shaping material, and the material is allowed to stand to allow the perfluoropolyether lubricating oil to penetrate into the interior of the second shaping material.
[0084] Similarly, the coating can also be carried out by spraying. The standing can be carried out at room temperature, and the standing time can be exemplarily not less than 24 hours.
[0085] In some embodiments, the molecular weight of the perfluoropolyether lubricant oil may be 10000 g / mol to 15000 g / mol.
[0086] It should be noted that if the molecular weight of the perfluoropolyether lubricant is too small, it will precipitate outward, resulting in failure; if the molecular weight of the perfluoropolyether lubricant is too large, it will be difficult for it to penetrate into the interior of the molding material, and even if it can penetrate, the corresponding penetration speed is slow, making it difficult to play an effective role.
[0087] The coating amount of perfluoropolyether lubricant can be 150mL / m 2 ~250mL / m 2 , such as 150mL / m 2 , 160mL / m 2 , 170mL / m 2 、180mL / m 2 , 190mL / m 2 , 200mL / m 2 , 210mL / m 2 , 220mL / m 2 , 230mL / m 2 , 240mL / m 2 or 250 mL / m 2 etc., or 150mL / m 2~250mL / m 2 Other values within the range.
[0088] If the amount of perfluoropolyether lubricant applied is too little, its effect will be limited; if the amount of perfluoropolyether lubricant applied is too much, after the material is saturated with the lubricant, too much perfluoropolyether lubricant will adhere to the surface of the material, which may easily cause the drag chain to adhere to too much lubricant, which is not conducive to subsequent maintenance and inspection.
[0089] As mentioned above, by coating the above amount of perfluoropolyether lubricating oil on the inner surface of the second shaping material, the dry friction between the wear-resistant drag chain protective material and the internal filling components (such as cables or air pipes, etc.) can be converted into wet friction, thereby reducing the friction coefficient and increasing the service life of the material; by coating the above amount of polytetrafluoroethylene emulsion on the outer side of the outer surface of the second shaping material and curing it at high temperature, the perfluoropolyether lubricating oil on the inner side of the second shaping material can be effectively prevented from precipitating to the outside. On the one hand, the perfluoropolyether lubricating oil can be confined to the inside of the second shaping material to extend its action time; on the other hand, the cleanliness of the surface of the wear-resistant drag chain protective material can be improved to achieve dust-free protection.
[0090] Furthermore, the above materials can be cut by a slitting machine according to actual needs.
[0091] It should be noted that other preparation conditions not disclosed in the present invention can refer to the relevant prior art and will not be described in detail here.
[0092] Correspondingly, the present invention also provides a wear-resistant drag chain protective material, which is prepared by the above-mentioned preparation method.
[0093] The wear-resistant drag chain protective material has few surface nodes, is smooth and wear-resistant. The entire wear-resistant drag chain protective material has high density, flexibility and wear resistance. However, the drag chain protective material made by stacking polytetrafluoroethylene films in the prior art not only has low density, but also has obvious surface fibers and poor wear resistance.
[0094] In some embodiments, the density of the wear-resistant drag chain protective material provided by the present invention is not less than 1.0 g / cm 3 , for example, it can be 1.0 g / cm 3 ~1.2g / cm 3 .
[0095] In some embodiments, the friction coefficient of the wear-resistant drag chain protective material does not exceed 0.1155, and the wear loss can be reduced to 0.004g.
[0096] In addition, the present invention also provides an application of the above-mentioned wear-resistant drag chain protective material, for example, it can be used in a drag chain device, and the internal filling components of the drag chain device can be cables or air pipes, etc.
[0097] Furthermore, the present invention also provides a cable, which includes a cable body, and a surface of the cable body is provided with a wear-resistant layer prepared from the above-mentioned wear-resistant drag chain protective material.
[0098] When the cable is a drag chain cable, the drag chain cable includes a drag chain in addition to a cable body with a wear-resistant layer, and the wear-resistant layer is connected to the inner side of the drag chain. That is, the inner surface of the wear-resistant drag chain protective material faces the cable body, and the outer surface of the wear-resistant drag chain protective material faces the drag chain.
[0099] The drag chain cable has high wear resistance and long service life.
[0100] In some preferred embodiments, the above-mentioned drag chain cable is a dust-free tank drag chain cable.
[0101] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0102] Example 1
[0103] This embodiment provides a wear-resistant drag chain protective material, and the preparation method thereof comprises the following steps:
[0104] S1: The polytetrafluoroethylene dispersion resin and the propellant are mixed and then extruded through a die to obtain an extruded base tape.
[0105] The mass ratio of the polytetrafluoroethylene dispersion resin to the propellant is 5:1, the propellant is an isoparaffin solvent, and specifically, the propellant product model is ISOPAR L. The extrusion molding pressure is 35 bar.
[0106] S2: The extruded base tape is calendered on a calendering device to obtain a calendered tape with a thickness of 0.6 mm.
[0107] S3: removing the propellant in the calendering belt, and then performing a stretching treatment to obtain a stretched film with a thickness of 25 μm.
[0108] Among them, the removal of the propellant is to put the calendered belt into a heating device, divide the temperature distribution in the box into steps from 100°C to 220°C according to the temperature interval of 10°C, and heat it to evaporate the propellant until it is completely removed.
[0109] The stretching treatment includes transverse stretching and longitudinal stretching. The transverse stretching has a stretching ratio of 9 times and is performed at 265°C. The longitudinal stretching has a stretching ratio of 14 times and is performed at 360°C.
[0110] S4: The stretch film is wound on the hard part and pressed for the first time, and then sintered and shaped for the first time to obtain the first shaped material.
[0111] Among them, the winding method is adopted, the hard part adopts a steel roller, and the thickness after winding is 0.8mm.
[0112] The pressure of the first pressing is 0.6 MPa, the time of the first pressing is 2 min, the temperature of the first sintering and shaping is 365° C., and the time of the first sintering and shaping is 15 min.
[0113] S5: The first shaped material is pressed for a second time, and then sintered for a second time to obtain a second shaped material.
[0114] The pressure of the second pressing can be 1.2 MPa, the time of the second pressing can be 2.5 min, the temperature of the second sintering and shaping can be 365° C., and the time of the second sintering and shaping can be 15 min.
[0115] S6: coating the outer surface of the secondary shaping material with tetrafluoro emulsion and curing the emulsion, and then coating the inner surface of the secondary shaping material with perfluoropolyether lubricating oil.
[0116] Among them, the spraying method is 300mL / m 2 Spray PTFE emulsion with a solid content of 60% on the outer surface of the second shaping material. The curing temperature is 230℃ and the time is 20min.
[0117] Spray at 200mL / m 2 A perfluoropolyether lubricating oil with a molecular weight of 10000 g / mol is sprayed on the inner surface of the second shaping material, and then allowed to stand at room temperature for 24 hours.
[0118] Example 2
[0119] This embodiment provides a wear-resistant drag chain protective material, and the preparation method thereof comprises the following steps:
[0120] S1: The polytetrafluoroethylene dispersion resin and the propellant are mixed and then extruded through a die to obtain an extruded base tape.
[0121] The mass ratio of the polytetrafluoroethylene dispersion resin to the propellant is 4:1, the propellant is an isoparaffin solvent, and specifically, the propellant product model is ISOPAR L. The extrusion molding pressure is 30 bar.
[0122] S2: The extruded base tape is calendered on a calendering device to obtain a calendered tape with a thickness of 0.5 mm.
[0123] S3: removing the propellant in the calendering belt, and then performing a stretching treatment to obtain a stretched film with a thickness of 20 μm.
[0124] Among them, the removal of the propellant is to put the calendered belt into a heating device, and divide the temperature distribution in the box into steps from 100°C to 220°C according to the temperature interval of 10°C / min, so as to volatilize the propellant until it is completely removed.
[0125] The stretching treatment includes transverse stretching and longitudinal stretching. The transverse stretching has a stretching ratio of 8 times and is performed at 250°C. The longitudinal stretching has a stretching ratio of 12 times and is performed at 320°C.
[0126] S4: The stretch film is wound on the hard part and pressed for the first time, and then sintered and shaped for the first time to obtain the first shaped material.
[0127] Among them, the winding method is adopted, the hard part adopts a steel roller, and the thickness after winding is 0.9mm.
[0128] The pressure of the first pressing is 0.2 MPa, the time of the first pressing is 1 min, the temperature of the first sintering and shaping is 350° C., and the time of the first sintering and shaping is 30 min.
[0129] S5: The first shaped material is pressed for a second time, and then sintered for a second time to obtain a second shaped material.
[0130] The pressure of the second pressing can be 0.5 MPa, the time of the second pressing can be 2 min, the temperature of the second sintering and shaping can be 350° C., and the time of the second sintering and shaping can be 30 min.
[0131] S6: coating the outer surface of the secondary shaping material with tetrafluoro emulsion and curing the emulsion, and then coating the inner surface of the secondary shaping material with perfluoropolyether lubricating oil.
[0132] Among them, the spraying method is 350mL / m 2 Spray the outer surface of the second shaping material with a PTFE emulsion with a solid content of 45%. The curing temperature is 220℃ and the time is 30min.
[0133] Spray at 150mL / m 2 A perfluoropolyether lubricating oil with a molecular weight of 12000 g / mol was sprayed on the inner surface of the second shaping material, and then allowed to stand at room temperature for 36 hours.
[0134] Example 3
[0135] This embodiment provides a wear-resistant drag chain protective material, and the preparation method thereof comprises the following steps:
[0136] S1: The polytetrafluoroethylene dispersion resin and the propellant are mixed and then extruded through a die to obtain an extruded base tape.
[0137] The mass ratio of the polytetrafluoroethylene dispersion resin to the propellant is 6:1, the propellant is an isoparaffin solvent, and specifically, the propellant product model is ISOPAR L. The extrusion molding pressure is 40 bar.
[0138] S2: The extruded base tape is calendered on a calendering device to obtain a calendered tape with a thickness of 0.7 mm.
[0139] S3: removing the propellant in the calendering belt, and then performing a stretching treatment to obtain a stretched film with a thickness of 30 μm.
[0140] Among them, the removal of the propellant is to put the calendered belt into a heating device, and divide the temperature distribution in the box into steps from 100°C to 220°C according to the temperature interval of 10°C / min, so as to volatilize the propellant until it is completely removed.
[0141] The stretching treatment includes transverse stretching and longitudinal stretching. The transverse stretching has a stretching ratio of 10 times and is performed at 280°C. The longitudinal stretching has a stretching ratio of 16 times and is performed at 400°C.
[0142] S4: The stretch film is wound on the hard part and pressed for the first time, and then sintered and shaped for the first time to obtain the first shaped material.
[0143] Among them, the winding method is adopted, the hard part adopts a steel roller, and the thickness after winding is 1.0mm.
[0144] The pressure of the first pressing is 1 MPa, the time of the first pressing is 1 min, the temperature of the first sintering and shaping is 380° C., and the time of the first sintering and shaping is 20 min.
[0145] S5: The first shaped material is pressed for a second time, and then sintered for a second time to obtain a second shaped material.
[0146] The pressure of the second pressing can be 1.5 MPa, the time of the second pressing can be 3 min, the temperature of the second sintering and shaping can be 380° C., and the time of the second sintering and shaping can be 20 min.
[0147] S6: coating the outer surface of the secondary shaping material with tetrafluoro emulsion and curing the emulsion, and then coating the inner surface of the secondary shaping material with perfluoropolyether lubricating oil.
[0148] Among them, the spraying method is 250mL / m 2 Spray PTFE emulsion with a solid content of 65% on the outer surface of the second shaping material. The curing temperature is 245℃ and the time is 15min.
[0149] Spray at 250mL / m 2 A perfluoropolyether lubricating oil with a molecular weight of 15000 g / mol is sprayed on the inner surface of the second shaping material, and then allowed to stand at room temperature for 30 hours.
[0150] Example 4
[0151] The present embodiment is different from the embodiment 1 in that the pressure and time of the second pressing are the same as the first pressing, that is, the pressure of the second pressing is 0.6 MPa, and the time of the second pressing is 2 min.
[0152] Example 5
[0153] The difference between this embodiment and embodiment 1 is that the propellant is kerosene.
[0154] Example 6
[0155] The difference between this embodiment and embodiment 1 is that the propellant is petroleum ether.
[0156] Example 7
[0157] The difference between this embodiment and embodiment 1 is that the propellant is paraffin.
[0158] Comparative Example 1
[0159] The difference between this comparative example and Example 1 is that step S5 is not performed between step S4 and step S6. That is, in this comparative example, the polytetrafluoroethylene emulsion is directly coated after the first sintering and shaping, and the second pressing is not performed.
[0160] Comparative Example 2
[0161] The difference between this comparative example and Example 1 is that in step S6, only the inner surface of the second shaping material is sprayed with perfluoropolyether lubricating oil, and the outer surface of the second shaping material is not coated with tetrafluoro emulsion and cured.
[0162] Comparative Example 3
[0163] The difference between this comparative example and Example 1 is that the perfluoropolyether lubricating oil and the tetrafluoro emulsion are directly mixed to obtain a mixed spray liquid which is then sprayed on the inner surface of the second shaping material.
[0164] Comparative Example 4
[0165] The difference between this comparative example and Example 1 is that there is no S6 step.
[0166] Comparative Example 5
[0167] The difference between this comparative example and Example 1 is that the solid content of the tetrafluoro emulsion is 40%.
[0168] Comparative Example 6
[0169] The difference between this comparative example and Example 1 is that the solid content of the tetrafluoro emulsion is 70%.
[0170] Comparative Example 7
[0171] The difference between this comparative example and Example 1 is that the spraying amount of the tetrafluoro emulsion is 200 mL / m 2 .
[0172] Comparative Example 8
[0173] The difference between this comparative example and Example 1 is that the spraying amount of the tetrafluoro emulsion is 400 mL / m 2 .
[0174] Comparative Example 9
[0175] The difference between this comparative example and Example 1 is that the molecular weight of the perfluoropolyether lubricating oil is 5000 g / mol.
[0176] Comparative Example 10
[0177] The difference between this comparative example and Example 1 is that the molecular weight of the perfluoropolyether lubricating oil is 20000 g / mol.
[0178] Comparative Example 11
[0179] The difference between this comparative example and Example 1 is that the coating amount of the perfluoropolyether lubricant is 100 mL / m 2 .
[0180] Comparative Example 12
[0181] The difference between this comparative example and Example 1 is that the coating amount of the perfluoropolyether lubricant is 300 mL / m 2 .
[0182] Comparative Example 13
[0183] The difference between this comparative example and Example 1 is that the mass ratio of the polytetrafluoroethylene dispersion resin to the propellant is 3:1.
[0184] Comparative Example 14
[0185] The difference between this comparative example and Example 1 is that the mass ratio of the polytetrafluoroethylene dispersion resin to the propellant is 8:1.
[0186] Test example
[0187] ① Taking the wear-resistant drag chain protective material prepared in Example 1 as an example, the surface and cross-sectional structure thereof were characterized by electron microscopy, and the results are as follows: Figure 1 and Figure 2 shown.
[0188] Depend on Figure 1 and Figure 2 It can be seen that the wear-resistant drag chain protective material prepared in Example 1 has lubricating oil adsorbed on the surface and inside of the material, the surface is treated with solvent, has few structural nodes and high smoothness, and the wear-resistant drag chain protective material has high density, flexibility and wear resistance.
[0189] In addition, a commercially available dust-free drag chain cable protection material was used as a control, and its surface was characterized by electron microscopy. The results are as follows: Figure 3 and Figure 4 shown.
[0190] Depend on Figure 3 and Figure 4 It can be seen that a dust-free drag chain cable protection material on the market has many surface nodes, low baseband density, obvious surface fibers and low surface smoothness.
[0191] ②, taking Example 1 as an example, the wear resistance of the second shaping material obtained in step S5 and the wear-resistant drag chain protection material obtained in step S6 were compared. The test standard was based on GB / T3960, the test temperature was 25°C, the ambient humidity was 55%, and the test load was 3kg. The results are as follows: Figure 5 and Figure 6 shown.
[0192] Depend on Figure 5 It can be seen that before surface treatment, the maximum friction coefficient corresponding to the second shaping material is 0.164969000, the minimum friction coefficient is 0.031903000, and the average value is 0.100130911; the mass before wear is 0.156g, the mass after wear is 0.145g, and the wear amount is 0.011g.
[0193] Depend on Figure 6 It can be seen that after surface treatment, the maximum friction coefficient of the wear-resistant drag chain protective material is 0.115495000, the minimum friction coefficient is -0.000660000, and the average value is 0.030600543; the mass before wear is 0.160g, the mass after wear is 0.156g, and the wear amount is 0.004g.
[0194] In addition, the commercially available dust-free drag chain cable protection material in ① was used as a control, and the wear resistance test was carried out according to the above test method. The results are as follows: Figure 7 shown.
[0195] Depend on Figure 7It can be seen that the maximum friction coefficient of the commercially available dust-free drag chain cable protection material is 0.776361000, the minimum friction coefficient is 0.283106000, and the average value is 0.50480273; the mass before wear is 0.135g, the mass after wear is 0.113g, and the wear amount is 0.022g.
[0196] It can be seen from the above results that the wear-resistant drag chain protective material provided by the embodiment of the present invention has high wear resistance.
[0197] ③. The wear-resistant drag chain protective materials obtained in Examples 2 to 7 and Comparative Examples 1 to 14 were tested for wear resistance according to the method in ②. The results are shown in Table 1.
[0198] Table 1 Test results
[0199]
[0200] It can be seen from Table 1 that the wear-resistant drag chain protective material prepared in the embodiment of the present invention has better wear resistance than the wear-resistant drag chain protective material prepared in the comparative example.
[0201] In summary, the preparation method of the wear-resistant drag chain protective material provided by the present invention is simple and easy to operate, and can effectively reduce the friction coefficient between the drag chain and the protective material. The obtained wear-resistant drag chain protective material has high density, good flexibility, smooth and wear-resistant surface, and high wear resistance, and is especially suitable for dust-free tank drag chain cables.
[0202] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a wear-resistant drag chain protective material, characterized in that: The following steps are involved: The polytetrafluoroethylene dispersion resin and the propellant are mixed and then extruded to obtain an extruded base tape; The extruded base strip is subjected to calendering treatment to obtain a calendered strip; a propellant in the calendered strip is removed, and then a stretching treatment is performed to obtain a stretched film; the stretched film is wound around a hard part and subjected to a first pressing, and then subjected to a first sintering and shaping to obtain a first shaped material; the first shaped material is subjected to a second pressing, and then subjected to a second sintering and shaping to obtain a second shaped material; Coating a tetrafluoro emulsion on the outer surface of the secondary shaping material and curing the emulsion, and then coating a perfluoropolyether lubricating oil on the inner surface of the secondary shaping material; The mass ratio of the polytetrafluoroethylene dispersion resin to the propellant is 4:1 to 6:1; The pressure of the first pressing is 0.2MPa~1MPa, and the time of the first pressing is 1min~2min; The temperature of the first sintering is 350℃~380℃, and the time of the first sintering is 15min~30min; The pressure of the second pressing is 0.5MPa~1.5MPa, and the time of the second pressing is 2min~3min; The temperature of the second sintering is 350℃~380℃, and the time of the second sintering is 15min~30min; The solid content of the tetrafluoro emulsion is 45% to 65%, and the coating amount of the tetrafluoro emulsion is 250 mL / m 2 ~350mL / m 2 ; The coating amount of the perfluoropolyether lubricant is 150 mL / m 2 ~250mL / m 2 The molecular weight of the perfluoropolyether lubricant is 10000 g / mol~15000 g / mol.
2. The preparation method according to claim 1, characterized in that: The propellant includes an alkane solvent.
3. The preparation method according to claim 1, characterized in that: The propellant includes at least one of kerosene, petroleum ether and paraffin.
4. The preparation method according to claim 1, characterized in that: The extrusion molding pressure is 30bar~40bar.
5. The preparation method according to claim 1, characterized in that: The thickness of the calendered belt is 0.5 mm to 0.7 mm.
6. The preparation method according to claim 1, characterized in that: The stretching treatment includes transverse stretching and longitudinal stretching; The transverse stretching is performed at a stretching ratio of 8 to 10 times and at a temperature of 250°C to 280°C. The longitudinal stretching has a stretching ratio of 12 to 16 times, and the longitudinal stretching is performed at a temperature of 320°C to 400°C.
7. The preparation method according to any one of claims 1 to 6, characterized in that The curing temperature is 220℃~245℃, and the curing time is 15min~30min.
8. A wear-resistant drag chain protective material, characterized in that: The method is prepared by any one of claims 1 to 7.
9. A cable, characterized in that: The cable comprises a cable body, and a wear-resistant layer prepared from the wear-resistant drag chain protective material according to claim 8 is provided on the surface of the cable body.
10. The cable according to claim 9, characterized in that The cable is a drag chain cable, which also includes a drag chain, and the wear-resistant layer is connected to the inner side of the drag chain.
Citation Information
Patent Citations
Preparation method of high-intensity teflon film
CN105666889A
Manufacturing method of expanded polytetrafluoroethylene face implant with coated surface
CN110898255A
Preparation process for unidirectionally stretching polytetrafluoroethylene film
CN111976173A
Polytetrafluoroethylene sealing material with low friction coefficient and low wear
CN115609989A